Analisi Strategi Pengembangan Pasar Tradisional Dalam Perspektif Ekonomi Islam (Studi Kasus Pasar Songgolangit Kabupaten Ponorogo) - Royyan Ramdhani Djayusman; Ahmad Lukman Nugraha; Khoirul Umam (Islamic Economics Journal, 2018)
This study aims to analyze traditional market development strategies by local governments from an Islamic economic perspective. This study used a qualitative method with a SWOT analysis. Qualitative methods are used to analyze the role of traditional market development from the perspective of Islamic Economics. Furthermore, the formulation of the strategy uses a SWOT analysis to obtain the development strategies in traditional market. The results of this study are; Firstly, the fluctuation of the total traders must be followed by the additional infrastructure. Secondly, the development strategy of the business in Songgolangit market can be done through two aspects; material and non-material aspects. The material aspect includes developing business capital. Non-material aspects include the development of business literacy and entrepreneurship. Thirdly, the role of local government in controlling and managing traditional markets is very important in issuing a local regulation (PERDA) for regulating the position, distance and operational time of street vendors (PKL), traditional markets and modern markets. Fourthly, the strategy of developing traditional markets through modernization of infrastructure and marketing utilizing technological progress.